Explaining the Components of Resilience in Patients with Chronic Pain: A Qualitative Content Analysis - Hajar Haghshenas; Maryam Shaygan; Nilofar Pasyar; Masoume Rambod (Wolters Kluwer Medknow Publications, 2024)
Background: Resilience is a psychological trait and a protective factor that plays a vital role in coping with Chronic Pain (CP). Despite its importance, research has yet to fully clarify the concept and components of resilience in patients with CP. Accordingly, the present study aims to explain the components of resilience in patients with CP. Materials and Methods: The current qualitative study used a conventional content analysis methodology. The research population included all patients with CP who were referred to clinics affiliated with Shiraz University of Medical Sciences (south of Iran) from August 2021 to August 2022. Participants were selected using the purposive sampling method. In-depth semi-structured interviews were conducted with 20 participants to collect information. Data analysis was conducted using MAXQDA 2020 software in conjunction with data collection efforts. Results: Generally, in the current study, 30 sub-sub-categories, 11 sub-categories, and five main categories were extracted as components of resilience in patients with CP. The main categories of resilience against CP included the following: 1. emotional self-regulation, 2. psychological flexibility, 3. self-care, 4. appeal to religion-spirituality, and 5. internal resources and individual competencies. Conclusions: The present study highlights the different physical, mental, and religious-spiritual strategies that may contribute to resilience against pain. The resilience components identified in this study provide a foundation for healthcare professionals, particularly nurses, to design and implement diverse pain management strategies that enhance adjustment to CP conditions.